Darius ebook - Ward, J.R (Black Dagger Brotherhood, 2023)
#1 New York Times bestseller J.R. Ward shares the passionate star-crossed love story of fan favorite, and original member of the Black Dagger Brotherhood, Darius. Darius, son of Marklon, isn't looking for love the night destiny comes to claim him. He's also not expecting to crash his new car. But when a human woman runs out into the road and he must swerve to avoid killing her...everything goes off course. Disillusioned by his King's lack of leadership and the losses in the war against the Lessening Society, Darius finds purpose in protecting a woman he cannot make his own. Love finds a way, however—until the truth of what he is comes out and she leaves him in horror. Unbeknownst to them both, Anne is carrying his young, a female who is destined to be Queen—and after a tragic reunion, he vows to protect their daughter. Resigned to perpetual sadness, he is determined to serve the memory of his beloved no matter the cost...unless by some miracle, fate sees fit to once again bring them together in this tale that is "full of drama, intrigue, and steamy restraint" ( Booklist ).